Mathematical values inculcation measurement model verses mathematics teachers’ length of service: a structural equation modeling analysis - Liman, Mukhtar Alhaji; Ibrahim, Mohd Burhan; Othman, Joharry (EuroJournals Publishing, Inc., 2012)
The importance of values inculcation in mathematics teaching and learning cannot be over emphasized. This is because values inculcation in mathematics teaching and learning enables learners understanding of the essence of the school’s mathematics. As such, this study investigates the direct and positive influence of mathematics teachers’ length of service in relation to values inculcation. A sample of n=509 mathematics teachers was drawn from the six states of the North Eastern Region of Nigeria. A self-constructed survey instrument was used to gather the data of the study. The findings of the study revealed that mathematics teachers’ length of service was not a moderating variable for effective values inculcation in mathematics classroom. The study contributed in the realization of values inculcation model for successful mathematical contents delivery.